Performance of basmati rice (Oryza sativa) under variable irrigation and nitrogen management - DASS, ANCHAL; KUMARI, KAVITA; DHAR, SHIVA; SUDHISHRI, S; SINGH, RAJIV KUMAR; DAS, T K; RANI, ALKA (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the rainy seasons (kharif) of 2021 and 2022 at research farm of ICAR- Indian Agricultural Research Institute, New Delhi to study the effect of irrigation regimes and integrated use of prilled urea and nano-urea as a source of N, on productivity and profitability of basmati rice (Oryza sativa L.). The experiment was conducted in a three-time replicated split-plot design (SPD) comprised of 3 irrigation regimes, viz. irrigation at 1, 3 and 6 days after disappearance of surface water (DADSW) assigned to main-plots and 4 N-management variants including; 100% RDN (recommended dose of N, 120 kg/ha); 75% RDN + 4% nano-urea (NU) 2 sprays (75% RDN + 2 NU); 50% RDN + 2 NU; and no-N (control) in sub-plots. Irrigating basmati rice 1 DADSW exhibited the highest panicle weight (2.67–3.09 g) and number of grains/panicle (115.9, 109.8), across the years, respectively that were significantly higher than 3 and 6 DADSW. The most delayed irrigation at 6 DADSW caused significant reduction in grain yield, the magnitude of reduction was 13–19% over irrigation at 3 DADSW and substantially by 23–28% over 1 DADSW. Fertilizing rice crop with 100% RDN and 75% RDN + 2 NU resulted in statistically similar yield attributes and grain yield; however, both were, significantly superior to 50% RDN + 2 NU and no-N. Net returns, benefit cost (B:C) ratio and monetary efficiency were significantly higher when crop was irrigated 1 DADSW than 3 and 6 DADSW. The N-management options followed the trend as RDN>75% RDN + 2 NU ˃50% RDN > no-N for all studied economic parameters.